Form and Function of Nomina in the Story of Si Bontar Mudar of Bakkara - Gaol, Elisabet Ibn; Simaremare, Juni Agus; Purba, Sintia; Tarihoran, Yuly (Dinamika Bahasa dan Budaya, 2024)
The purpose of this study is to describe the form and function of nouns in the story of Sibontar Mudar of Bakkara. The type of research method used by the author is the literature method. Data collection techniques in this research are reading, recording, processing the content in the story. The source of data analysis that researchers use is the storybook "the story of sibontar mudar from bakkara". The results of this study can be concluded that in the form of nouns in the Sibontar Mudar story are basic nouns and derived nouns where the function of basic nouns is to show the names of people, objects, places, or concepts in general while the function of derived nouns shows nouns derived from verbs or adjectives. So that it can be used in the function of nouns in Sibontar Mudar stories is to indicate people, objects, places, or concepts in Sibontar Mudar stories that compose sentences, convey meaning, and enrich the diversity of language for good communication and help in broadening and deepening our understanding of the world around us, while providing flexibility and richer expression in language. KEY WORDS: Form and Function of Nomina; From the Story of Sibontar Mudar of Bakkara